(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
The national security policy of Switzerland is based upon the specifics of the Swiss country and it is distinguished with great complicacy and complexity. Hence, the examination of the security policy should be founded of its complete comprehension and thorough perception of the conditions in order to avoid improvisation and partiality. This signifies that the security policy should be rationally founded and to synthetize the efforts of all of the security actors in order to provide the necessary level of security, for the society, the nation, and for the citizens. Generally, the altered nature of security threats conditioned the need for redefining the security policy of Switzerland and also imposed for adoption of new approaches toward security. Accepting such reality, Switzerland has to adjust to the new circumstances for the protection of the national interests and the neutrality policy. The Adaptation of the security system in the new security environment has to be a reflection and result of the evident general overall inclusion of all the subjects, which are authorized for enforcing the security policy.